2020
DOI: 10.5650/jos.ess20131
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Investigation of Metal-Dipeptide Complex with Ninhydrin in the Absence and Presence of CTAB Micelles

Abstract: Introduction Formation of Ruhemann s purple is widely used to detect amino groups in simple organic compounds, proteins and peptides. For these purposes usually, a spray reagent is prepared in situ in a laboratory environment. A variety of commercial spray reagents are available and these contain ninhydrin, one or more metal ions and surfactants in aqueous and non-aqueous media. Such sprays are used for developing TLC plates and in detecting finger prints for forensic work. The response to these reagents depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The micellar phase also affected the quantity of the intermediates. Overall, the analysis suggested that the surfactant had a co-operative effect of the formation of the imine intermediate [ 21 ]. A similar co-operative effect of the surfactant on the intermediate has been observed between CTAB and p -nitroacetophenone (detected via NMR studies) in the Morita-Baylis-Hillman reaction of ketones [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The micellar phase also affected the quantity of the intermediates. Overall, the analysis suggested that the surfactant had a co-operative effect of the formation of the imine intermediate [ 21 ]. A similar co-operative effect of the surfactant on the intermediate has been observed between CTAB and p -nitroacetophenone (detected via NMR studies) in the Morita-Baylis-Hillman reaction of ketones [ 22 ].…”
Section: Introductionmentioning
confidence: 99%